34‐4: Figure of Merit for Optimizing the Performance of Uniform Lying Helix Cholesteric Liquid Crystals. Issue 1 (May 2017) - Tan, Guanjun; Lee, Yun-Han; Gou, Fangwang; Hu, Minggang; Lan, Yi-Fen; Tsai, Cheng-Yeh; Wu, Shin-Tson
Abstract : The figure of merit (FoM) is defined to evaluate the performance of ULH devices. The trade‐offs between operation voltage, transmittance, and response time in uniform lying helix (ULH) cholesteric liquid crystals (CLC) are investigated. Excellent agreement between theory and experiment is achieved. The viewing angle of ULH displays is also studied. Our results give first quantitative demonstration that ULH exhibits a similar viewing angle to IPS. After phase compensation, the isocontrast ratio of ULH can reach >100:1 over 85° viewing cone.